Desenvolvimento de um protocolo de avaliação de fatores de risco extralaborais para a identificação de dor osteomuscular - Scandelari, Lília Inês Kühnl (2016)
The aim of this study was to develop an Extra Work Risk Factor Assessment Protocol for musculoskeletal pain through a prospective and exploratory survey conducted with the permanent employees of the Town Hall of Curitiba. Methodology: The study was conducted in two phases. In the first phase, it was developed and implemented the Work and Extra Work Activities Questionnaire which permitted the determination of the labor factors of increased risk of developing musculoskeletal pain in this population, and to investigate the presence of the most prevalent extra work risk factors in the literature. Further, we made the correlation between the questionnaire answers with the data on musculoskeletal pain reported by employees in Ergonomics Census and the Cause and Effect Diagram was held. Statistical analyzes were performed with the statistical package GRAPHPAD PRISM and was considered a significance level of 5% (α = 0.05). In the second phase of the research, we developed the LIKS Extra Work Risk Assessment Protocol, designed from the structure of the Questionnaire of Work and Extra Work activities, prioritizing extra work risk factors, in the shape of objective responses, containing a quantitative scale of risk for the development or aggravation of the musculoskeletal pain. Results: It was obtained as a potential cause for musculoskeletal pain the age of 40 years (p = 0.001) and workstation (p = 0.008). In this study, physical activity and 6 hours of sleep or more were considered as a protective factor and insomnia, the inappropriate use of computers, tablets and mobile home and personal stress were considered relative risk factors. The evaluation of gender questions, occupation, second occupation, sleeping position, ways to go and come to work and video game use was not statistically significant. Conclusions: Extra work risk factors probably interact with the development of musculoskeletal pain. It is important to know and get more employee information during regular review is important in the health-disease process. Prioritize the causes and factors involved in musculoskeletal pain complaints are of paramount importance for the prevention, early diagnosis and referrals to appropriate treatment and health promotion.